Factors Associated With Mortality and Response to Extracorporeal Photopheresis in Lung Allograft Recipients With Bronchiolitis Obliterans Syndrome. Issue 5 (May 2019) - Karnes, Hope E.; Schindler, Emily I.; Morrell, Matt; Hachem, Ramsey R.; Berman, Keith; Vedantham, Suresh; Atkinson, Jeff; Spitznagel, Edward; Despotis, George John
Abstract : Background: This study was designed to identify factors associated with clinical response to extracorporeal photopheresis (ECP) and mortality after ECP in lung allograft recipients with bronchiolitis obliterans. Methods: Forced expiratory volume in 1 second (FEV1) values obtained 6 months before (baseline) and 6 months after initiation of ECP were used to plot the linear relationship between FEV1 versus time before and after ECP. Response to ECP was assigned when a positive integer was derived after subtracting the baseline rate of decline from the rate of decline 6 months after ECP. Univariate and multivariate logistic regression analyses were used to identify demographic, treatment-related factors or spirometric parameters that may be associated with response to ECP or mortality at either 6 or 16 months after initiation of ECP. Results: Forced expiratory volume in 1 second just before ECP was associated with mortality ( P = 0.007) at 16 months after ECP initiation. An FEV1 of 1.50 L or less had a sensitivity of 87% and specificity of 60% to identify patients who died within 16 months after ECP initiation. Patients whose FEV1 decline exceeded 40 mL/month were 12 times more likely to have a response to ECP ( P = 0.0001). Patients whose decline in FEV1 before ECP was statistically significant ( P < 0.05) were nearly 10 times ( P = 0.008) more likely to respond to ECP. Conclusions: Forced expiratory volume in 1 second is an important predictor of mortality, and the response to ECP is influenced by both the extent (>40 mL/mo) and statistical significance of the relationship between FEV1 versus time before ECP initiation. Therefore, earlier bronchiolitis obliterans detection and more timely implementation of ECP (ie, when FEV1 values >1.5 L) should be considered especially in patients with a more aggressive rate of decline of lung function.